Holy matter : changing perceptions of the material world in late medieval Christianity - Ritchey, Sara Margaret (Ithaca : Cornell University Press, 2014)
"A magnificent proliferation of new Christ-centered devotional practices--including affective meditation, imitative suffering, crusade, Eucharistic cults and miracles, passion drama, and liturgical performance--reveals profound changes in the Western Christian temperament of the twelfth century and beyond. This change has often been attributed by scholars to an increasing emphasis on God's embodiment in the incarnation and crucifixion of Christ. In Holy Matter, Sara Ritchey offers a fresh narrative explaining theological and devotional change by journeying beyond the human body to ask how religious men and women understood the effects of God's incarnation on the natural, material world. She finds a remarkable willingness on the part of medieval Christians to embrace the material world--its trees, flowers, vines, its worms and wolves--as a locus for divine encounter"--
The mirror of holy virginity -- Virginitas and viriditas -- Clare of Assisi and the ligna of crucifixion -- The Franciscan bough -- An estranged wilderness.
Includes bibliographical references and index.
Description based on print version record.
Master record variable field(s) change: 082
Keywords: Nature -- Religious aspects -- Catholic Church -- History of doctrines -- Middle Ages, 600-1500.; Spiritual life -- Christianity -- History of doctrines -- Middle Ages, 600-1500.; Natural theology -- History of doctrines -- Middle Ages, 600-1500.; Theology, Doctrinal -- History -- Middle Ages, 600-1500.; RELIGION / Christian Theology / General; Nature - Religious aspects - Catholic Church - History of doctrines - Middle Ages, 600-1500.; Electronic books; Electronic books